Lost bullet - Rose, Malcolm (London : Kingfisher, 2005)
When there's a murder mystery to solve, The Authorities send in their top forensic team. Luke Harding runs fast, thinks even quicker and has the best detective instincts around. His right-hand robot is Malc, equipped with lasers, scanners and technology for finding clues at the toughest of crime scenes. Together, Luke and Malc have the talent to crack any crime - and a good joke, too. Welcome to the thrilling world of Traces. Aged just 16, Luke Harding is the youngest Forensic Investigator ever. In the slums of London, Luke and Malc investigate a doctor's murder. They find a bullet wound to her head, but rain has washed away the bullet - and all other clues. As more innocent victims die, pressure builds on Luke and Malc to find the culprit before the bizarre shooting spree becomes an all-out massacre.
Formerly CIP.
Keywords: Forensic scientists -- Juvenile fiction; Children's stories; Suspense fiction